2019
DOI: 10.3390/ani9030079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on Selected Life-History Traits of Black Soldier Fly (Hermetia illucens) Reared on Two Common Urban Organic Waste Streams in Kenya

Abstract: In sub-Saharan Africa, urban populations are projected to increase by 115% in the coming 15 years. In addition, economic growth and dietary shifts towards animal source foods have put high pressure and demand on agricultural production. The high ecological footprint of meat and dairy production, as well as high feed costs, prevent the livestock sector from meeting the increasing demand in a sustainable manner. Insects such as the black soldier fly (BSF) have been identified as potential alternatives to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 59 publications
3
53
1
15
Order By: Relevance
“…The functions that are modelled in this work as cases or switching functions, Eqs (11), (12), (17) and (18), are realized as logistic functions in the actual implementation of the model in…”
Section: Implementation Of Switching Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functions that are modelled in this work as cases or switching functions, Eqs (11), (12), (17) and (18), are realized as logistic functions in the actual implementation of the model in…”
Section: Implementation Of Switching Functionsmentioning
confidence: 99%
“…A total of four data sets (T1-T4) representing the influence of temperature on larvae development was obtained from [10,11]. These four data sets represent the temperature dependency under four different feed types and was used to obtain the parameters for models Eqs (6) and (7).…”
Section: Temperature Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Insect growth and development are also affected by temperature, light, and humidity. Certain appropriates temperature (27.5–37.5 °C) [57,58], light levels [59,60] and humidity (70%) [61] are more conducive to spawning, emergence, and conversion of organic waste in this insect. Several studies have found that hydrolytic proteins and organophosphates from Bacillus subtilis are present in the gut and skin of H. illucens larvae [62,63].…”
Section: Biological Morphologymentioning
confidence: 99%
“…The knowledge about life history traits and molecular biology of a species plays very important role to establish breeding industry and mass scale production. Additionally, previous studies have been supervised on life history traits of BSF on different substrates to utilize industrialization in temperate zone (Jucker et al 2017, Shumo et al 2019, Gobbi et al 2013. In this study, molecular identification using the barcode region of the mitochondrial cytochrome oxidase I (mtCOI) gene and life cycle of local species, H. illucens from Bangladesh were investigated under laboratory condition.…”
Section: Introductionmentioning
confidence: 99%